KETERAMPILAN MENULIS KREATIF CERPEN MENGGUNAKAN MEDIA AUDIO SISWA KELAS XII SMAN 1 KECAMATAN PAYAKUMBUH - Linda, Wirda (Universitas Ahmad Dahlan, 2017)
Writing skills is activities of language serves to produce written language. Writing can improve intelligence, develop initiative, creativity,, stimulate the willingness and ability to gather information. Students skills in short stories writing activities is still lacking. This things because teachers use less attractive media. Thus, this study uses audio media to increase students interest in writing. This study aimed to describe the shost story intrinsic elements and the use of capital letters in Creative Short Story Writing Skills Using Media Audio Class XII SMAN I Payakumbuh District.This research is a quantitative research using descriptive method. The study population class XII students totaling 217 consists of 8 classes. Writer to perform sampling with random random sampling techniques. The instrument of this study is to test performance. Data analysis in the study: to check the results to write short stories, analyze the data and provide a score based on indicators, and put forward the test results to the classification skills by using a scale of 10.Results showed that average value of 90.8 are in the range of 86-95% with good qualification. Creative writing skills are evaluated from two short stories specified indicators are: (1) short story creative writing skills in terms of the intrinsic elements of the short story is the 100 that are in the range of 96-100% with impeccable qualifications; (2) The short story creative writing skills in terms of capitalization was 80.8% are in the 76-85 range with good qualifications. Thus, we can conclude the students are already capable in writing short stories as well as the use of capital letters in writing.